Mucociliary clearance in patients with chronic autonomic failure. Issue 9 (September 1980) - Jenkins, P; Pavia, D; Bateman, J R; Clarke, S W; Citron, K M; Bannister, R
Abstract : Mucociliary clearance was measured in four patients with chronic autonomic failure and normal ventilatory function using a method of scanning the clearance of inhaled polystyrene particles tagged with 99mTc. Previous surgical and experimental evidence has suggested that autonomic denervation might be expected to impair clearance. However, the four patients in this study showed no significant difference in clearance rate compared to groups of sex-matched control subjects. A fifth patient was found to have impaired mucociliary clearance. However she had the symptoms and ventilatory function of smoking-related chronic obstructive bronchitis, a condition which has previously been shown to impair mucociliary clearance.